Identifying Service, Research and Policy priorities for preventing the impacts of family adversity on children’s mental health: An Australian national resource allocation study with professional and lived experience experts - Harriet Hiscock; Ashraful Kabir; Suzy Honisett; Tamara Morris; Leanne Constable; Suzie Forell; Sue Woolfenden; Sharon Goldfeld; Anthony Jorm (Australian and New Zealand Journal of Public Health, 2024)
Objectives: The objective of this study was to develop Service, Research and Policy priorities to prevent the impact of family adversity on child mental health and determine comparative priorities of diverse stakeholders to those with lived experience of adversity. Methods: Value-weighting approach conducted in a staged process: (i) professionals and experts with lived experience from health, education, justice and social care sectors attended a national symposium to identify priorities for family adversity and mental health and (ii) a subsequent resource allocation survey gathered views from participants and external experts on symposium priorities. Results: Consensus was reached on priorities. Service priorities included establishing intersectoral hubs for children and families and early childhood nurse home-visiting programs. Research priorities included scaling up evidence-based interventions and evaluating cross-sector, flexible funding models for services addressing childhood adversity. Policy priorities included developing evidence-based policies with evaluation and implementation plans and flexible funding models to support integrated care. Conclusions: Our results provide detailed and actionable clarity on next steps to address family adversities. Implications for Public Health: The priorities call for a focus on cross-sectoral approaches to preventing or mitigating the effects of family adversity. The current Australian policy environment provides a timely opportunity to action the proposed interventions.